Penentuan Setting Level Berdasarkan Faktor-Faktor yang Berpengaruh terhadap Kebocoran Produk Wellhead menggunakan Metode Taguchi di PT BDT - Irma Agustiningsih Imdam; Dewi Auditiya Marizka; Indah Kurnia Mahasih Lianny; Wilda Sukmawati; Irva Syariatun Nisa (NUCLEUS, 2023)
Setting the Wellhead product level needs to be done as bbest as possible to avoid leaks when drilling for oil and natural gas which are caused by pressure differences during drilling. PT BDT as one of the companies that makes wellheads always tries to make the products they produce according to consumer desires. Even though PT BDT has tried its best, it has still received complaints from customers, because of leaks that occurred during drilling and had to incur costs for product replacement. The stages in the research process begin with conducting a field study to identify existing problems in the company and then continue with conducting a literature study to identify theories that can be used as solutions to overcome these problems. The method used to prevent weelhead leaks is the Taguchi method which consists of of three stages, namely stages: planning, implementation, and analysis. The influencing factors used are the amount of sand, the amount of paint, the thickness of the sun blasting, and the pressure of the compressor. This stage is carried out to calculate the influence of each factor used on the quality characteristics used, namely nominal is the best. Based on the results of the wellhead pressure test carried out after the experiment, the Signal to Noise Ratio (SNR) can be calculated. The best level results were obtained to prevent wellhead leaks by setting all levels at level 2, namely the amount of sand was 3.3 grams, the amount of paint was 4.5 liters, and the thickness of the sun was (1.5 mm). The amount of quality loss function incurred by the company due to the wellhead leak was IDR 759,900